The Impact of Broken Home Conditions on The Spirit of Learning Ability and Morals in Grade IX Students at MTs Al-Husainy, Bima City - Yuliyanti (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to determine the impact of broken home family conditions on students' enthusiasm for learning in the subject of Aqidah Akhlak in grade IX students at Mts Al HusainyKta Bima. The background of this study is based on the importance of the role of the family as the first and main environment in shaping the character and enthusiasm for learning of children. Inharmonious family conditions, such as divorce or separation of parents, can cause emotional stress that has an impact on students' motivation and interest in learning, especially in subjects related to moral and spiritual values. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The subjects of the study were grade IX students who came from broken homes. The results of the study showed that most students from broken homes experienced a decrease in enthusiasm for learning, especially in the subject of Aqidah Akhlak. Factors such as lack of parental attention, family conflict, and emotional instability are the main causes of the decrease in students' enthusiasm for learning. This study concludes that broken home family conditions have a real impact on students' enthusiasm for learning Aqidah Akhlak, so the active role of teachers and school counselors is needed in providing guidance and moral support to affected students.